A Linguistic Analysis of the Croatian Verb brijati - Broz, Vlatko (2003)
This paper examines different linguistic aspects of the verb brijati in urban spoken Croatian. It explores an unusually wide range of meanings that this verb and its derivatives have in authentic sentences taken from Internet newsgroups and interviews with a great number of native speakers of Croatian. The verb’s polysemic structure is briefly described but the semantic motivation for extending its meaning remains a puzzle.
ENG